2018
DOI: 10.1016/j.jinorgbio.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

CW EPR parameters reveal cytochrome P450 ligand binding modes

Abstract: Cytochrome P450 (CYP) monoxygenses utilize heme cofactors to catalyze oxidation reactions. They play a critical role in metabolism of many classes of drugs, are an attractive target for drug development, and mediate several prominent drug interactions. Many substrates and inhibitors alter the spin state of the ferric heme by displacing the heme's axial water ligand in the resting enzyme to yield a five-coordinate iron complex, or they replace the axial water to yield a nitrogen-ligated six-coordinate iron comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…This suggests that the substrate binds to CYP199A4 but does not displace the resting state aqua ligand in agreement with the crystal structure. 33,35 In the case of 4-(pyridin-3-yl)-benzoic acid all three g-values of the major component shift, with large gx and gz changes, which supports coordination of the pyridinyl nitrogen of the substrate to the ferric paramagnetic center (Figure 6). 29 However, to definitively determine the proximal ligand on the basis of the gvalue shifts alone carries uncertainty, and thus we sought to identify the proximal ligand using high-resolution pulsed EPR methods.…”
Section: Substrate Binding In Frozen-solution As Determined By Eprmentioning
confidence: 73%
See 2 more Smart Citations
“…This suggests that the substrate binds to CYP199A4 but does not displace the resting state aqua ligand in agreement with the crystal structure. 33,35 In the case of 4-(pyridin-3-yl)-benzoic acid all three g-values of the major component shift, with large gx and gz changes, which supports coordination of the pyridinyl nitrogen of the substrate to the ferric paramagnetic center (Figure 6). 29 However, to definitively determine the proximal ligand on the basis of the gvalue shifts alone carries uncertainty, and thus we sought to identify the proximal ligand using high-resolution pulsed EPR methods.…”
Section: Substrate Binding In Frozen-solution As Determined By Eprmentioning
confidence: 73%
“…23,24,25,26 A ferric P450 heme can be high-spin (HS, S = 5/2), or low-spin (LS, S = 1/2), and these electronic ground states can be distinguished by optical and EPR spectra. [26][27][28][29][30][31][32][33] The UV-vis spectrum of a substrate-bound cytochrome P450 is dependent on the nature of heme ligation. A type I change (blue shift; 418 nm to 390 nm) is associated with an increase in HS character upon ligand binding to the enzyme, whereas a reverse type I spectral change (red shift; 390 nm to 418 nm) reflects a change from more HS to LS character.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse type I spectral shifts associated with ligand binding reinforcing water interaction with the heme iron typically have a trough at ~390 nm and a peak at ~422 nm (Ouellet et al, 2011). EPR studies have shown that 1,2,4-triazoles do not form water-bridged complexes in CYP3A4 (Lockart et al, 2018). Type II difference spectra associated with ligand nitrogen binding to the heme iron have trough at ~410 nm and a peak at ~434.…”
Section: Discussionmentioning
confidence: 99%
“…Although direct azole coordination to iron is observed, there is also a second arrangement in which fluconazole forms a hydrogen bond to a water molecule that is in turn coordinated to the heme iron. This water-bridged binding mode has only been observed in a few other bacterial P450 enzyme structures (Poulos and Howard, 1987;Ouellet et al, 2011;Fonvielle et al, 2013), but EPR data suggests this binding mode may be more common in solution (Lockart et al, 2018). Thus, at least two different azole binding modes are documented, though both are inhibitory (Seward et al, 2006).…”
Section: Dmd #82032mentioning
confidence: 93%